The Pengaruh Penerapan Technological Knowledge melalui E-modul “Sistem Koordinasi” terhadap Hasil Belajar Kognitif Tingkat Tinggi dan Kemampuan Berkolaborasi Siswa - Syafitrii, Nadia; Masitah; Akhmad; Maasawet, Elsje Theodora; Nasution, Ruqoyyah (PendIPA Journal of Science Education, 2025)
This study aimed to determine the effect of the application of Technological Knowledge through the e-module "Coordination System" on the results of high-level cognitive learning and collaboration skills of class XI students in biology subjects at SMA Negeri 5 Samarinda. This study was quantitative with a Quasi Experiment type of research with a nonequivalent control group design. On the results of high-level cognitive learning, the results of the t-test were obtained with a significance value of 0.010<0.05 and the results of the N-Gain test were 64.31% with a fairly effective category. On the ability to collaborate, the results of the t-test were obtained with a significance value of 0.000<0.05 and an average value of 77.58% with a good category. Thus, it is concluded that the application of Technological Knowledge through the e-module "Coordination System" has a significant effect on the results of high-level cognitive learning and collaboration skills of class XI students in biology subjects at SMA Negeri 5 Samarinda.